pemanfaatan mendeley dan sumber rujukan artikel dalam mendukung dalam penyusunan skripsi pada mahasiswa semester VIII penjaskesrek stkip pgri trenggalek - Saputra, Riko galang saputra Galang (STKIP PGRI SUMENEP, 2023)
A common problem that occurs among students, including Semester VIII students of Penjaskesrek STKIP PGRI Trenggalek, is in making a list of references for previous research to support the thesis that is being made. Beginning writers usually get caught up in plagiarism by accident due to being careless in making reference lists. The reference source itself is used as the basis used in thesis writing which can be obtained from various kinds of literature. Seeing the importance of referral sources and relatively many locations, software that manages these referral sources is needed, namely properly. Therefore, this study aims to determine the extent to which and article reference sources support the preparation of the thesis. The type of research used is qualitative research with a descriptive approach. Data collection techniques using observation, interviews, questionnaires, and documentation. Data analysis techniques using data collection, data reduction, data presentation, and conclusions. The results of this study are Mendeley application is very beneficial for its users, the presence of article reference sources is also very useful, and the use of Mendeley applications and article reference sources in the preparation of the thesis is declared useful.